A Systematic Review and Meta-Analysis of the Prevalence and Risk Factors of Depression in Type 2 Diabetes Patients in China - Liu, Xiaobo; Li, Yuxi; Guan, Li; He, Xia; Zhang, Huiling; Zhang, Jun; Li, Juan; Zhong, Dongling; Jin, Rongjiang (Frontiers in Medicine, 2022)
Background The prevalence of type 2 diabetes mellitus (T2DM) is increasing in China. Depression in patients with T2DM interferes with blood glucose management, leads to poor treatment outcomes, and has a high risk of dementia and cardiovascular event. We conducted this systematic review and meta-analysis to evaluate the prevalence of depression in patients with T2DM in China and explore potential risk factors associated with depression in T2DM. Methods We conducted a literature search in MEDLINE/PubMed, EMBASE, the Cochrane Library, the Chinese Biomedical Literature Database (CBM), the China National Knowledge Infrastructure (CNKI), the Chinese Science and Technology Periodical Database (VIP), and the Wanfang Database from their inception to February 25, 2022 to include population-based, cross-sectional surveys that investigated the prevalence of depression in Chinese T2DM patients and studied possible risk factors. Gray literature and reference lists were also manually searched. We used the Agency for Healthcare Research and Quality methodology checklist to assess the risk of bias in the included studies. Two reviewers screened studies, extracted data, and evaluated the risk of bias independently. The primary outcome was the pooled prevalence of depression in Chinese T2DM patients, and the secondary outcomes included potential risk factors for depression in T2DM patients. R (version 3.6.1) and Stata (version 12.0) software were used for data synthesis. Results We included 48 reports that identified 108,678 subjects. Among the included reports, 4 were rated as low risk of bias, 40 moderate risks of bias, and 4 high risks of bias. The prevalence of depression in T2DM patients in China was 25.9% (95% CI 20.6%−31.6%). The prevalence of depression was higher in women (OR = 1.36, 95% CI 1.19–1.54), subjects ≥60 years (OR = 1.56, 95% CI 1.14–2.14), with a primary school or lower education (vs. middle or high school education (OR = 1.49, 95% CI 1.16 – 1.92); vs. college degree or higher education (OR = 1.84, 95% CI 1.16 – 2.92), with a duration of T2DM ≥ 10 years (OR = 1.68, 95% CI 1.11–2.54), with complications (OR = 1.90, 95% CI 1.53–2.36), insulin users (OR = 1.46, 95% CI 1.09–1.96) and individuals living alone (OR = 2.26, 95% CI 1.71–2.98). T2DM patients with current alcohol use had a lower prevalence of depression (OR = 0.70, 95% CI 0.58–0.86). Prevalence varied from 0.8 to 52.6% according to different instruments used to detect depression. Conclusion The prevalence of depression in T2DM patients is remarkable in China. Potential risk factors of depression in T2DM patients included women, age ≥ 60 years, low educational level, complications, duration of diabetes ≥ 10 years, insulin use, and living alone. High-quality epidemiological investigations on the prevalence of depression in Chinese T2DM patients are needed to better understand the status of depression in T2DM. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42020182979.